Development of Vilnius street network / Vilniaus gatvių tinklo formavimas - Juškevičius, Pranciškus (Journal of Civil Engineering and Management, 1996)
The planning of city street network expansion faces a new problem in Lithuania – indetermination of the city development. The model of street network and its loading has demonstrated the possible variant of relatively balanced development of urban street network. But in spite of this it does not close the increasing gap between the need for street network capacities and possibilities available. The main strategic trend in street network development is gradual forming the street network subsystem of the highest category. It should be supplemented by the reconstruction of the existing crossings as well as by creating new regulation equipment of high quality. One of the components of street network development strategy is the restriction of traffic and parking in the city centre and old town. Article in Lithuanian. First Published Online: 26 Jul 2012